Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1016/j.autrev.2009.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Malignancies in systemic lupus erythematosus

Abstract: The purpose of this review is to underline important advancements in the understanding of cancer risks in systemic lupus erythematosus (SLE). In SLE, there is an increased risk of specific kinds of malignancy. For example, the risk of non-Hodgkin's lymphoma is increased several-fold in SLE versus the general population. In addition, heightened risks for lung cancer, thyroid cancer and cervical dysplasia in SLE have been found. Some have postulated that immunosuppressive drugs play a role, as well as other impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 65 publications
(43 reference statements)
1
42
0
Order By: Relevance
“…On the other hand, the screening rate for cervical cancer is lower in people with lupus (Kiss et al, 2010).…”
Section: Inflammatory Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the screening rate for cervical cancer is lower in people with lupus (Kiss et al, 2010).…”
Section: Inflammatory Diseasementioning
confidence: 99%
“…Several studies have investigated the role of inflammatory diseases in cervical cancer (Bernatsky et al, 2009;Kiss et al, 2010;Simon et al, 2015). The results of a population-based cohort study showed that women with rheumatoid arthritis and systemic lupus erythematosus are 1.5 times more likely to develop cervical dysplasia and cervical cancer (Kim et al, 2014).…”
Section: Inflammatory Diseasementioning
confidence: 99%
“…There is evidence that, in certain autoimmune diseases, there is an increased risk of developing lymphoid malignancies. The background of this phenomenon includes common genetic predisposition, viral infection (e.g., EBV virus), use of immunosuppressive agents, persistent antigen stimuli, chronic inflammation, uncontrolled B cell proliferation, and defected apoptosis [28].…”
Section: Genetic Aberrationsmentioning
confidence: 99%
“…The role of immunosuppressive therapy is controversial; it may impair immune defence resulting in an increased risk of lymphomagenesis. However, SLE patients who have never been treated with immunosuppressive agents have the highest rate of NHL incidence during the first year from diagnosis, suggesting that the increased risk is not related to cumulative doses of therapy (Kiss et al, 2010). A nested case-cohort study performed to assess the HR for cancer within a multi-site international SLE cohort after exposure to immunosuppressive drugs (anti-malarial drugs, systemic glucocorticoids, NSAIDs, aspirin) showed an adjusted HR for overall cancer risk of 0.82.…”
Section: Pathogenesismentioning
confidence: 99%